X+3x+4(x-1)=-12

Simple and best practice solution for X+3x+4(x-1)=-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X+3x+4(x-1)=-12 equation:


Simplifying
X + 3x + 4(x + -1) = -12

Reorder the terms:
X + 3x + 4(-1 + x) = -12
X + 3x + (-1 * 4 + x * 4) = -12
X + 3x + (-4 + 4x) = -12

Reorder the terms:
-4 + X + 3x + 4x = -12

Combine like terms: 3x + 4x = 7x
-4 + X + 7x = -12

Solving
-4 + X + 7x = -12

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + X + 4 + 7x = -12 + 4

Reorder the terms:
-4 + 4 + X + 7x = -12 + 4

Combine like terms: -4 + 4 = 0
0 + X + 7x = -12 + 4
X + 7x = -12 + 4

Combine like terms: -12 + 4 = -8
X + 7x = -8

Add '-7x' to each side of the equation.
X + 7x + -7x = -8 + -7x

Combine like terms: 7x + -7x = 0
X + 0 = -8 + -7x
X = -8 + -7x

Simplifying
X = -8 + -7x

See similar equations:

| 0.6x+5.3=4.4 | | 0.6+5.3=4.4 | | -2=3m-5m | | 2cos^2x+sinx=5 | | 3(x-2)=3x+12 | | 2-3x(x-1)= | | 70-(3x+50)=2-5x | | x/17-7x/17=30/17 | | W-10=-25 | | 2+3(x-2)=5x-10 | | 0.7x-7.7(3.6+3.7x)=-241.703 | | X/11=-2/13 | | -4(x+2)=-63 | | 3x+9x-12=180 | | R-11=3 | | -125.994=-6.9(-2.8n-3.3) | | 3(x-6)-4x=20 | | -12+2y=10 | | X+7X^2-63=8 | | 125.994=-6.9(-2.8n-3.3) | | 4x^2+72x+308=0 | | -82.93884=5.8(2.38k-1.9) | | f(x)=-x^2-x+6 | | 2a+4b+8c= | | x+2(x-6)=x-11 | | 3(6+8)=48 | | 2a+4b+15= | | 2a+4b-15= | | 2(9x+5)=12x-2 | | x-7+3x=18 | | -95.552=-3.2(3.2n+6.5) | | 3x+75=360 |

Equations solver categories